Rev-erbα agonist SR9009 protects against cerebral ischemic injury through mechanisms involving Nrf2 pathway - Sheng, Mingyue; Chen, Xun; Yu, Yan; Wu, Qi; Kou, Junping; Chen, Gangling (Frontiers in Pharmacology, 2023)
Backgrounds: The circadian clock protein Rev-erbα is a crucial regulator of circadian rhythms that affects multiple molecular, cellular, and physiology pathways that control susceptibility, injury, and recovery in the neurological disorders. Emerging evidence suggest that Rev-erbα plays a key role in the inflammation and oxidative stress, two pivotal mechanisms in the pathogenesis, progression, and recovery process of ischemic stroke. However, it remains inconclusive whether Rev-erbα activation is protective against ischemic brain damage. Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway, a master regulator of inflammatory and oxidative responses. Our study aimed to determine whether pharmacological activation of Rev-erbα by SR9009 protects against acute ischemic brain damage partly via Nrf2 pathway. Methods: Adult mice were pretreated with SR9009 or Nrf2 inhibitor all-trans-retinoic acid (ATRA) for 3 days prior to Sham or middle cerebral artery occlusion (MCAO) operation. After ischemia for 1 h and reperfusion for 24 h, the neurological function and cerebral infarction volume were determined, superoxide dismutase (SOD) activity, malondialdehyde (MDA) content and glutathione peroxidase (GSH-PX) activity in serum were detected by kit. The mRNA and/or protein level of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), inducible nitric oxide synthase (iNOS), Period (Per)1, Brain and muscle arnt-like1 (Bmal1), Circadian locomotor output cycles kaput (Clock), Rev-erbα, Nrf2, heme oxygenase-1 (HO-1) and quinone oxidoreductase 1 (NQO1) in cerebral cortex were detected by q-PCR and Western blot. Results: We confirmed that SR9009 activated Rev-erbα gene in the cerebral cortex under basal condition. At 24 h after reperfusion, SR9009 ameliorated acute neurological deficits, reduced infarct volume. Meanwhile, the inflammatory TNF-α, IL-1β, iNOS and MDA content levels were significant decreased, SOD and GSH-PX activity were obviously increased, which were markedly blunted (or abolished) by ATRA. SR9009 enhanced the induction of Nrf2 and its downstream target genes HO-1 and NQO1 after ischemic insult. In addition, we found that SR9009 restored Rev-erbα, Bmal1, Clock, Per1 genes expression in the cerebral cortex under ischemic condition. Conclusion: Taken together, Rev-erbα activation by SR9009 protects against ischemic stroke damage, at least, partly through Nrf2 pathway.